Interprofessionalism in the Clinical Clerkship of the Medical Profession - A. Adila Permata Abdullah; Ida Royani; Windy Nurul Aisyah (Journal of Asian-african Focus in Health, 2026)
Clinical clerkship is a crucial stage in medical education because students begin to move from classroom based learning into real clinical practice, where collaboration with nurses, pharmacists, and other health professionals becomes essential. This article reviews interprofessionalism in the clinical clerkship of the medical profession by examining how Interprofessional Education or IPE supports the development of collaborative competence among medical students. This study used a literature review design with an analytical approach. Relevant articles were searched through PubMed, Google Scholar, and ScienceDirect using keywords related to interprofessional education, interprofessional learning, medical education, and clinical clerkship. The reviewed literature shows that interprofessional learning in clinical clerkship occurs through three main phases, namely entering unfamiliar professional territory, making sense of other professional roles, and achieving meaningful participation in patient care teams. The findings indicate that IPE generally improves students’ attitudes, communication, teamwork, and collaborative behavior. However, the understanding of roles and responsibilities across professions remains a persistent challenge, especially when students rely on informal assumptions or stereotypes about other health professions. Structured IPE activities, institutional support, faculty development, and explicit role clarification are important factors that strengthen interprofessional competence. Conversely, limited resources, scheduling difficulties, and professional stereotypes hinder effective implementation. This review concludes that interprofessionalism in clinical clerkship should not be treated as an incidental learning experience, but as a deliberately structured component of medical education that prepares future physicians to work collaboratively, communicate effectively, and contribute to safer and more patient centered healthcare delivery